2018
DOI: 10.1080/15384101.2018.1520567
|View full text |Cite
|
Sign up to set email alerts
|

BLM’s balancing act and the involvement of FANCJ in DNA repair

Abstract: Timely recruitment of DNA damage response proteins to sites of genomic structural lesions is very important for signaling mechanisms to activate appropriate cell cycle checkpoints but also repair the altered DNA sequence to suppress mutagenesis. The eukaryotic cell is characterized by a complex cadre of players and pathways to ensure genomic stability in the face of replication stress or outright genomic insult by endogenous metabolites or environmental agents. Among the key performers are molecular motor DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 138 publications
(199 reference statements)
0
5
0
Order By: Relevance
“…Study on the network of mRNAs and miRNAs in BLM-deficient cells has indicated that G-quadruplex motifs are enriched at transcription start sites, and especially within first introns of differentially expressed mRNAs, in Bloom syndrome compared with normal cells, which may drive the pathogenesis of Bloom syndrome [260]. With the development of research on BLM and G-quadruplexes, more and more functions and mechanisms are revealed, including in DNA double-strand breaks repair [240], excessive sister chromatid exchange [241], and chromosomal rearrangements [242]. Another important member of this subfamily is the Werner-syndrome-associated helicase (WRN), which shows similar functions to BLM [243,244].…”
Section: G-quadruplexes and Their Binding Proteinsmentioning
confidence: 99%
“…Study on the network of mRNAs and miRNAs in BLM-deficient cells has indicated that G-quadruplex motifs are enriched at transcription start sites, and especially within first introns of differentially expressed mRNAs, in Bloom syndrome compared with normal cells, which may drive the pathogenesis of Bloom syndrome [260]. With the development of research on BLM and G-quadruplexes, more and more functions and mechanisms are revealed, including in DNA double-strand breaks repair [240], excessive sister chromatid exchange [241], and chromosomal rearrangements [242]. Another important member of this subfamily is the Werner-syndrome-associated helicase (WRN), which shows similar functions to BLM [243,244].…”
Section: G-quadruplexes and Their Binding Proteinsmentioning
confidence: 99%
“…Furthermore, a role for FANCJ besides from the FA pathway, has been postulated with a function in the removal of G-quadruplex (G4) DNA structures[12,13]. Interestingly, a direct interaction of FANCJ and the RecQ helicase BLM was shown, and both helicases seem to cooperate in response to replicative stress [14,15]. These various functions hint to a multifunctional role of FANCJ in the maintenance of genome stability.…”
Section: Introductionmentioning
confidence: 99%
“…FANCJ is also phosphorylated at threonine 1133 in response to replication stress, facilitating a direct interaction with TOPBP1, and promotion of an ATR-dependent checkpoint in response to replication stress (29). Additional DNA repair proteins, including MRE11, RPA, and BLM bind within the FANCJ carboxy terminus (881-1249), and although the binding parameters remain to be fully characterized, these interactions have been shown to regulate FANCJ enzyme activity (30)(31)(32)(33)(34). While only MLH1 binding has been shown to be essential for ICL resistance, other FANCJ interactions including BRCA1 and TOPBP1 modulate its DNA repair and checkpoint activities, respectively, in a manner that could be critical for tumor suppression (reviewed in (35)).…”
Section: Introductionmentioning
confidence: 99%